Effect of Er:YAG Laser and Sandblasting in Recycling of Ceramic Brackets - Yassaei, Soghra; Aghili, Hossein; Hosseinzadeh Firouzabadi, Azadeh; meshkani, hamidreza (Journal of Lasers in Medical Sciences, 2017)
Introduction: This study was performed to determine the shear bond strength of rebonded mechanically retentive ceramic brackets after recycling with Erbium-Doped Yttrium Aluminum Garnet (Er:YAG) laser or sandblasting. Methods: Twenty-eight debonded ceramic brackets plus 14 intact new ceramic brackets were used in this study. Debonded brackets were randomly divided into 2 groups of 14. One group was treated by Er:YAG laser and the other with sandblasting. All the specimens were randomly bonded to 42 intact human upper premolars. The shear bond strength of all specimens was determined with a universal testing machine at a crosshead speed of 0.5 mm/min until bond failure occurred. The recycled bracket base surfaces were observed under a scanning electron microscope (SEM). Analysis of variance (ANOVA) and Tukey tests were used to compare the shear bond strength of the 3 groups. Fisher exact test was used to evaluate the differences in adhesive remnant index (ARI) scores. Results: The highest bond strength belonged to brackets recycled by Sandblasting (16.83 MPa). There was no significant difference between the shear bond strength of laser and control groups. SEM photographs showed differences in 2 recycling methods. The laser recycled bracket appeared to have as well-cleaned base as the new bracket. Although the sandblasted bracket photographs showed no remnant adhesives, remarkable micro-roughening of the base of the bracket was apparent. Conclusion: According to the results of this study, both Er:YAG laser and sandblasting were efficient to mechanically recondition retentive ceramic brackets. Also, Er:YAG laser did not change the design of bracket base while removing the remnant adhesives which might encourage its application in clinical practice